Expanding the Spectrum of Renal Tumors in Children: Primary Renal Myoepithelial Carcinomas With a Novel EWSR1-KLF15 Fusion. (March 2016) - Cajaiba, Mariana M.; Jennings, Lawrence J.; Rohan, Stephen M.; Leuer, Katrin M.; Anagnost, Miran R.; Fahner, James B.; Fulton, Barbara K.; Geller, James I.; Perlman, Elizabeth J.
Abstract : We report the first 2 examples of primary renal myoepithelial carcinoma (MEC), both occurring in children. Both tumors had the unique morphologic features, immunophenotype, and EWSR1 gene rearrangements supporting the diagnosis. In keeping with the previous observations of an aggressive behavior in pediatric MEC, both cases presented with advanced local stage and distant metastases at the time of diagnosis. The EWSR1 translocation partner was identified as the Kruppel-like factor 15 ( KLF15 ) gene in both tumors, and the novel EWSR1-KLF15 gene fusion transcripts were verified using reverse transcription polymerase chain reaction and Sanger dideoxy sequencing. So far, a role for KLF15 in carcinogenesis has not been established, in contrast to other members of the Kruppel-like family of transcription factors, and no rearrangements involving this gene have been documented to our knowledge. These findings expand the spectrum of pediatric renal tumors to include MEC. The characterization of novel EWSR1-KLF15 fusion transcripts carries important diagnostic implications, as well as clues to understand the pathogenesis of these neoplasms.